Review of dietary patterns and gastric cancer risk: epidemiology and biological evidence - Pu, Ke; Feng, Yang; Tang, Qian; Yang, Guodong; Xu, Chuan (Frontiers in Oncology, 2024)
Due to rapid research expansion on dietary factors and development of cancer prevention guidelines, the field of dietary pattern and its relationship to cancer risk has gained more focus. Numerous epidemiology studies have reported associations between Gastric Cancer (GC) and both data-driven posteriori dietary pattern and priori dietary pattern defined by predetermined dietary indexes. As dietary patterns have evolved, a series of patterns based on biological markers has advanced, offering deeper insights into the relationship between diet and the risk of cancer. Although researches on dietary patterns and cancer risk are booming, there is limited body of literature focusing specifically on GC. In this study, we compare the similarities and differences among the specific components of dietary patterns and indices, summarize current state of knowledge regarding dietary patterns related to GC and illustrate their potential mechanisms for GC prevention. In conclusion, we offer suggestions for future research based on the emerging themes within this rapidly evolving field.